2003
DOI: 10.1002/eat.10141
|View full text |Cite
|
Sign up to set email alerts
|

A dialectical behavior therapy program for people with an eating disorder and borderline personality disorder—description and outcome

Abstract: Full DBT is an expensive and demanding treatment but deserves consideration for patients with an eating disorder and co-morbid borderline personality disorder and self-harm. There is a need for a more systematic and thorough evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 7 publications
4
58
0
5
Order By: Relevance
“…To date, several preliminary studies have shown that DBT may be a valuable intervention for ED patients with comorbid BPD and those with chronic ED symptoms. [24][25][26][27] As described by others, these data suggest that patients with severe EDs and additional comorbid diagnoses may require more comprehensive interventions. 1,2 In light of these findings, and with the aim of further exploring the efficacy of DBT for complex patients with EDs, the Multidiagnostic Eating Disorder-DBT (MED-DBT) Program was developed and is currently being evaluated in a specialized outpatient treatment center (see Ref.…”
Section: Introductionsupporting
confidence: 69%
“…To date, several preliminary studies have shown that DBT may be a valuable intervention for ED patients with comorbid BPD and those with chronic ED symptoms. [24][25][26][27] As described by others, these data suggest that patients with severe EDs and additional comorbid diagnoses may require more comprehensive interventions. 1,2 In light of these findings, and with the aim of further exploring the efficacy of DBT for complex patients with EDs, the Multidiagnostic Eating Disorder-DBT (MED-DBT) Program was developed and is currently being evaluated in a specialized outpatient treatment center (see Ref.…”
Section: Introductionsupporting
confidence: 69%
“…Telephone skill-coaching is an integral component in some (e.g. Wisniewski & Kelly, 2003;McCabe et al, 2004;Palmer et al, 2003), but not all (e.g. Telch et al, 2001;Safer et al, 2001b), DBT treatments for eating disorders described in the literature.…”
Section: Discussionmentioning
confidence: 98%
“…There is a growing body of literature on the application of DBT to the treatment of clients with eating disorder as the primary diagnosis (e.g. Palmer et al, 2003;Telch, Agras, & Linehan, 2000Safer, Telch, & Agras, 2001a;Wisniewski & Kelly, 2003). Furthermore, it has been shown that personality disorder symptoms predict poor treatment outcome in eating disorder clients (Rossiter, Agras, Telch, & Schneider, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Die Effektivität des Ansatzes ist durch mehrere kontrollierte, randomisierte Studien gut belegt [Linehan et al, 1991[Linehan et al, , 1993. Abwandlungen des Originalansatzes der ambulanten DBT sind bis heute für unterschiedliche Patientengruppen erschienen: Jugendliche [Miller et al, 1997], Patienten mit Suchtstörungen [Linehan et al, 1999] oder Essstörungen [Palmer et al, 2003] und forensische Patienten [Evershed, 2003]. Eine weitere Abwandlung des Originalansatzes stellten Barley und Mitarbeiter [1993] vor.…”
Section: Schlüsselwörterunclassified